(untitled) (Medico Legal Update, 2020)
?- Thalassemia major is an inherited blood disorder caused by drop or total absence of beta globin chains. Patients with this blood disorder are repeatedly needed to blood transfusion to survive. There are many experimental and clinical evidence that suggested that the oxidative stress and free radical plays an important role in thalassemia. The aim of the present study was to investigate the level of antioxidant enzymes and trace element with interleukin 6 in ? thalassemia major patients. The blood samples were obtained from 50 patients (30 with ?-thalassemia major and 20 healthy controls).The serum levels of MDA, GSH, Vitamin (E, C), trace element (Fe, Zn, Cu, Se) and antioxidant enzymes (SOD, CAT, GPx) and interleukin 6 were anaslysed using conventional methods. The results showed that the level of MDA, Fe, Cu and interleukin 6 were significantly increased (P<0.05), whereas the activities of GSH, Vitamin (E, C), trace element (Zn, Se) and antioxidant enzymes (CAT, GPx) were decreased significantly (P<0.05) in ?-thalassemia major patients compared with healthy control. This results suggested that the ? thalassemia patients disease activity `and progress could be investigated by determining the oxidative stress marker, trace element and interleukin 6 levels.